2001
DOI: 10.1097/00003246-200107000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Induced abdominal compartment syndrome increases intracranial pressure in neurotrauma patients: A prospective study

Abstract: Increased IAP causes a significant rise in ICP in head trauma patients. This effect seems to be the result of an increase in intrathoracic pressure, which causes a functional obstruction to cerebral venous outflow. Routine assessment of IAP may help clinicians to identify remediable causes of increased ICP. Caution should be used when applying laparoscopic techniques in neurotrauma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
12

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(96 citation statements)
references
References 21 publications
3
78
1
12
Order By: Relevance
“…Increased venous pressure could perhaps reduce the pressure gradient for cerebral venous drainage. Our findings agree with the current literature (6)(7)(8) and broaden the knowledge of body compartments.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Increased venous pressure could perhaps reduce the pressure gradient for cerebral venous drainage. Our findings agree with the current literature (6)(7)(8) and broaden the knowledge of body compartments.…”
Section: Discussionsupporting
confidence: 93%
“…Intra-thoracic (ITP) and intra-abdominal pressures (IAP) are known to influence ICP. (6)(7)(8) However, the magnitude of this effect and its clinical relevance, except in acute neurological diseases, are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This is potentially relieved by abdominal decompression as well as by central volume expansion and PEEP ventilation. 153 The dynamics of the effect of IAP on ICP are different if there is a concomitant traumatic or nontraumatic brain injury, 154 although in patients with brain trauma and IAH, a more liberal approach towards decompressive laparotomy and a more judicious delay in closure of the open abdomen when it is employed is indicated.…”
Section: Miscellaneous Pathophysiology and Intra-abdomi-nal Hypertensionmentioning
confidence: 99%
“…Elevations in central venous and jugular venous pressures result in increased resistance to cerebral outflow, which causes an increase in ICP and decrease in CPP. 35 Animal experiments have demonstrated that IAH of >20 mmHg causes significant increases in ICP and decreases in CPP. Additionally, elevations in CSF lactate and interleukin-6 were also seen, suggesting the associated presence of cerebral ischemia.…”
Section: Concurrent Abdominal Injurymentioning
confidence: 99%